ChemInform Abstract: A Novel Copper‐Rich Open‐Framework Chalcogenide Constructed from Octahedral Cu4Se6 and Icosahedral Cu8Se13 Nanoclusters. Issue 22 (12th May 2016) - Yang, Huajun; Wang, Le; Hu, Dandan; Lin, Jian; Luo, Li; Wang, Hongxiang; Wu, Tao
Abstract: The Cu‐rich open‐framework chalcogenide (pipH)10 [Cu16 Sn6 Se19 (Se2 )6 ] (pip: piperidine) is prepared by solvothermal reaction of the elements and piperidine (Cu:Sn:Se = 1.8:4.3:25, autoclave, 180 °C, 12 d; 19% yield).